Sodium battery positive electrode material and preparation method and application thereof
By covering the carbon layer on the surface of the matrix material of the sodium electropositive electrode material and controlling the form and form of the carbon coating, the problems of insufficient conductivity and cyclic stability of the existing materials are solved, and the effects of high capacity and good cyclic stability are achieved.
Patent Information
- Application Number
- CN202411985570.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing sodium electropositive electrode materials have shortcomings in electrical conductivity and cycle stability, and commonly used preparation methods such as solid-phase ball milling, wet ball milling and spray drying have problems with mixing uniformity and composition segregation, resulting in limited performance improvement.
By covering the carbon layer on the surface of the matrix material and controlling the form of carbon coating, the coordination between partial coating and full coating is adopted to combine dot-shaped and sheet-shaped carbon coating forms to improve the conductivity of the sodium-electrode material and the transmission efficiency of sodium ions.
The excellent conductivity and stable circulation performance of sodium-electrode material are achieved, with high capacity performance and good circulation stability.
Smart Images

Figure CN119786573A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a sodium positive electrode material and a preparation method and application thereof. Background Art
[0002] The development of sodium battery cathode materials is imperative. The main routes are layered oxides, Prussian white, and polyanion materials. Among them, polyanion materials have attracted much attention due to their stable structure, high operating voltage, good safety performance, cycle stability, and high specific capacity. Among the many polyanion materials, iron-based polyanion materials, which have abundant resources, are the most popular due to their high specific capacity. 3+ / Fe 2+ Reversible redox couples and polyanions are considered to be potential cathode materials for sodium-ion batteries due to their strong electronegativity and inductive effect, as well as their low production cost and high operating voltage.
[0003] CN112510198A discloses a positive electrode active material, an aqueous sodium ion battery and an electronic device. The chemical formula of the positive electrode active material is Na x Fe y (PO4) m (Y) n , where Y is F - OH - , O 2- 、N 3- 、P2O7 4- 、SO4 2- 、NO3 - 、CO3 2- 、C2O4 2- One of the following, 1≤x≤4, 1≤y≤3, 1≤m≤3, 1≤n≤4; the iron-based mixed polyanionic sodium-embedded compound, compared with the existing transition metal oxides, Prussian blue compounds and vanadium-based polyanionic compound positive electrode materials, not only has low cost, better electric capacity and cycle stability, but also does not contain CN - Or harmful ions of V, will not affect the environment. However, the poor conductivity of polyanion materials themselves will lead to poor electrochemical performance of sodium positive electrode materials, and they often need to be carbon coated to obtain excellent electrochemical performance.
[0004] The solid phase ball milling method commonly used in the preparation of iron-based sodium positive electrode materials is to mix the carbon source, iron source, and sodium source, and then achieve uniform mixing of the materials by ball milling, and then sinter to obtain the iron-based sodium positive electrode material. However, this method lacks the uniformity of the mixing of materials, resulting in the sample being unable to effectively exert its performance. Although the use of wet ball milling can improve the uniformity of material mixing to a certain extent, there is still a large component segregation problem, which has a very limited improvement in the performance of the sample. At the same time, the use of wet ball milling will greatly increase the experimental steps, resulting in increased costs. The spray drying method can also effectively solve the problem of uneven dispersion of the sodium source and the iron source, but there will still be uneven dispersion of the conductive carbon. In addition, the spray drying method has high production costs and low efficiency, and is not suitable for large-scale industrial production. Therefore, although the performance of the sodium iron sulfate prepared by the spray drying method has been improved to a certain extent, it is still not the best choice. In addition, there are preparation methods such as hot solvent method, anti-solvent method, freeze drying method, etc., but these methods are too complicated and not suitable for large-scale production processes. In addition, the carbon coating effect of the iron-based sodium battery positive electrode material obtained by the above preparation method is poor, thereby affecting the conductivity of the obtained sodium battery positive electrode material and affecting the transmission of sodium ions in the positive electrode material.
[0005] Therefore, providing a sodium battery positive electrode material with excellent performance is an urgent problem to be solved. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a sodium positive electrode material and its preparation method and application. The sodium positive electrode material provided by the present invention is coated with a carbon layer on the surface of the base material, which improves the stability and conductivity of the material. Further, the form of carbon coating is regulated, and the partial coating and full coating of the carbon layer on the surface of the base material are used in combination with the specific form of partial carbon coating. While improving the conductivity of the sodium positive electrode material, it also improves the transmission of sodium ions inside the material, so that the sodium positive electrode material can have the advantages of excellent capacity performance and stable cycle performance.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a sodium-based positive electrode material, the sodium-based positive electrode material comprising a base material and a carbon layer coated on a surface of the base material;
[0009] The chemical formula of the matrix material is Na 2+2x Fe 2-x M3, where M is a polyanion, 0≤x<2;
[0010] The sodium-based positive electrode material includes a first sodium-based positive electrode material and a second sodium-based positive electrode material. The carbon layer on the surface of the base material in the first sodium-based positive electrode material is fully coated, and the carbon layer on the surface of the base material in the second sodium-based positive electrode material is partially coated. The coating morphology of the partially coated carbon layer includes dots and / or flakes.
[0011] The sodium battery positive electrode material provided by the present invention is coated with a carbon layer on the surface of the base material, which reduces the contact between the base material and the air, can improve the stability of the sodium battery positive electrode material, and can improve the conductivity of the material, making up for the defect of the poor conductivity of the polyanion positive electrode material itself, thereby improving the electrochemical performance of the sodium battery positive electrode material. The present invention further regulates the carbon coating on the surface of the base material to exist in two forms: full coating and partial coating. The two cooperate with each other. While improving the conductivity of sodium ferrous sulfate, due to the presence of the partially coated sodium positive electrode material, the base material in the sodium positive electrode material can directly contact with the electrolyte in the subsequent application process, reducing the hindering effect on the diffusion of sodium ions, ensuring that the sodium positive electrode material exerts the corresponding capacity, and thus can jointly improve the capacity performance and cycle performance of the sodium positive electrode material; secondly, the present invention regulates the morphology of the partially coated carbon layer in the sodium positive electrode material into a point-like and / or sheet-like shape. The point-like carbon coating has less hindrance to the transmission of sodium ions, which is beneficial to the deintercalation of sodium ions in the sodium positive electrode material, thereby improving the capacity performance of the battery material. The sheet-like carbon coating is beneficial to the conduction of electrons because the contact mode between the base material and the carbon is surface contact; further, through the combination of the point-like and sheet-like carbon coating morphologies, the obtained sodium positive electrode material has a good electronic conduction effect, and can also ensure the effective transmission of sodium ions, thereby improving the comprehensive electrochemical performance of the sodium positive electrode material.
[0012] The sodium-based cathode material provided by the present invention is coated with a carbon layer on the surface of a base material, which can improve the stability of the sodium-based cathode material and improve the electrical conductivity of the material itself, and further control the form of carbon coating. Through the mutual coordination of partial carbon coating and full carbon coating on the base material, the partial coating is further controlled to adopt a specific form of sheet and / or point, which can ensure that the sodium-based cathode material has excellent electrical conductivity and stability, and can also promote the effective transmission of sodium ions in the material, improve the deintercalation of sodium ions inside the material, so that the sodium-based cathode material can have multiple advantages of excellent capacity performance and stable cycle performance.
[0013] Preferably, said M comprises a sulfate anion.
[0014] Preferably, with the total mass of the sodium positive electrode material being 100wt%, the mass percentage of the carbon layer coated on the surface of the base material is 0.1-20wt%, for example, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt% or 20wt%.
[0015] Preferably, in the sodium electric positive electrode material, the mass ratio of the first sodium electric positive electrode material to the second sodium electric positive electrode material is (5-50):(50-95), for example, 5:95, 10:90, 20:80, 30:70, 40:60 or 50:50, etc.
[0016] Preferably, the thickness of the carbon layer in the first sodium cathode material and the carbon layer in the second sodium cathode material are independently selected from 1-50 nm, for example, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, etc.
[0017] The sodium-ion positive electrode material of the present invention regulates the thickness of the carbon layer within a reasonable range, which can ensure effective coating of the base material to ensure the improvement of the conductive properties of the base material. At the same time, it avoids the effect of excessively thick carbon layer coating on the sodium ion deintercalation in the positive electrode material, thereby causing the performance of the sodium-ion positive electrode material to deteriorate.
[0018] Preferably, the first sodium cathode material is a core-shell structure.
[0019] Preferably, the second sodium battery positive electrode material comprises any one or a combination of at least two of a positive electrode material having a carbon layer coated in a dot-shaped form, a positive electrode material having a carbon layer coated in a sheet-shaped form, or a positive electrode material having a carbon layer coated in a dot-shaped and sheet-shaped form.
[0020] Different types of second sodium cathode materials in the present invention can be mixed in any proportion.
[0021] Preferably, when the partial coating of the carbon layer is in a dotted form, the diameter of the carbon layer is 1-100nm, excluding 100nm, such as 1nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 99nm, etc.; the gap distance between the carbon layers is 1-200nm, such as 1nm, 5nm, 10nm, 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm or 200nm, etc.
[0022] Preferably, when the partially coated morphology of the carbon layer is flaky, the diameter of the carbon layer is 100-500nm, and the gap distance between the carbon layers is 1-200nm, for example, 1nm, 5nm, 10nm, 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm or 200nm, etc.
[0023] Preferably, when the partially coated carbon layer is in the form of dots and flakes, the diameter of the dot-shaped carbon layer is 1-100nm, excluding 100nm, such as 1nm, 10nm, 20nm, 40nm, 60nm, 80nm or 99nm, etc.; the diameter of the flake-shaped carbon layer is 100-500nm, such as 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc.
[0024] Preferably, when the partial coating of the carbon layer is in the form of dots and sheets, the gap distance between the dot-shaped carbon layer and the sheet-shaped carbon layer is 1-200nm, for example, 1nm, 5nm, 10nm, 20nm, 40nm, 60nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm or 200nm, etc.
[0025] In the present invention, the “gap distance between carbon layers” refers to the distance between the partially coated carbon layers on the surface of the substrate material and the partially coated carbon layers. Figure 1 , where d represents the gap area between carbon layers, 1 is the surface of the matrix material, and 2 is the carbon layer.
[0026] Preferably, the compaction density of the sodium positive electrode material at 3T pressure is 1.8-2.36 g / cm 3 , for example 1.8 g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 , 2.0g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 , 2.15g / cm 3 , 2.2g / cm 3 , 2.25g / cm 3 , 2.3g / cm 3 or 2.36 g / cm 3 wait.
[0027] Preferably, the specific surface area of the sodium positive electrode material is 5-30m2 / g, for example 5m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 24m 2 / g, 26m 2 / g, 28m 2 / g or 30m 2 / g, etc.
[0028] In the present invention, the compaction density and specific surface area of the sodium battery positive electrode material both refer to the performance of the overall sodium battery positive electrode material.
[0029] Preferably, the sodium battery positive electrode material also includes free carbon.
[0030] Preferably, the total carbon content in the sodium cathode material is 100wt%, and the carbon content coated on the surface of the matrix material is 10-99wt%, for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 95wt% or 99wt%, etc.
[0031] Preferably, the total carbon content in the sodium cathode material is 100wt%, and the carbon content of the free carbon is 1-50wt%, for example, 1wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt% or 50wt%.
[0032] Preferably, the sodium battery cathode material comprises primary particles and secondary particles.
[0033] It should be noted that, on the basis of satisfying that the sodium-based positive electrode material is divided into a first sodium-based positive electrode material (the carbon layer on the surface of the base material is completely coated) and a second sodium-based positive electrode material (the carbon layer on the surface of the base material is partially coated), there is no specific limitation on the specific coating form of the primary particles and the secondary particles of the sodium-based positive electrode material, including but not limited to the first sodium-based positive electrode material and / or the second sodium-based positive electrode material, and those skilled in the art can make a selection as needed.
[0034] Preferably, the size of the primary particles is 0.001-1 μm, for example, 0.001 μm, 0.005 μm, 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm or 1 μm.
[0035] Preferably, the size of the secondary particles is 0.01-100 μm, for example 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, etc.
[0036] The secondary particles in the present invention mainly exist in three forms: one is the secondary particles formed by agglomeration, which are formed by agglomeration of at least two primary particles, and the mass of the secondary particles formed by agglomeration of the primary particles accounts for 5-50wt% of the total mass of all the secondary particles; the second is the secondary particles formed by carbon connection, which uses carbon as a link to connect at least two primary particles at the same time to form secondary particles, and the mass of the secondary particles formed by carbon connection accounts for 5-30wt% of the total mass of all the secondary particles; the third is secondary particles composed of multiple particles including both agglomerated particles and carbon-connected particles, and the mass of this form of secondary particles accounts for 10-90wt% of all the secondary particles.
[0037] Preferably, based on the total content of the total particles of the sodium positive electrode material as 100%, the content of the primary particles is 5-90wt%, for example, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 90wt%, etc.
[0038] Preferably, the total content of the total particles of the sodium positive electrode material is 100wt%, and the content of the secondary particles is 1-80wt%, for example, 1wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%, etc.
[0039] In a second aspect, the present invention provides a method for preparing the sodium positive electrode material according to the first aspect, the preparation method comprising the following steps:
[0040] (1) solid-phase mixing a first raw material with an organic carbon source, and sintering the mixture to obtain an intermediate having in-situ carbon coating; the first raw material provides sodium ions and polyanions;
[0041] (2) performing a secondary solid phase mixing of the intermediate having in-situ carbon coating with a second raw material and an antioxidant to obtain a precursor material; the second raw material provides ferrous ions and polyanions;
[0042] (3) Pressing and sintering the precursor material to obtain the sodium positive electrode material.
[0043] In the present invention, the first raw material is used to provide sodium ions and polyanions, wherein a raw material containing both sodium ions and polyanions can be selected, or two raw materials containing sodium ions and polyanions respectively can be selected.
[0044] In the present invention, the second raw material is used to provide ferrous ions and polyanions, wherein one raw material containing both ferrous ions and polyanions can be selected, or two raw materials containing ferrous ions and polyanions respectively can be selected.
[0045] The preparation method provided in the present invention combines the processes of primary solid-phase mixing-sintering-secondary solid-phase mixing-pressing and sintering, and can regulate the form and morphology of carbon coating in sodium-based positive electrode materials, ensure the simultaneous existence of full and partial carbon coating, and regulate the morphology of partial carbon coating, which is beneficial to improving the deintercalation of sodium ions in the sodium-based positive electrode materials while improving the conductivity of the sodium-based positive electrode materials, thereby improving the performance of the sodium-based positive electrode materials.
[0046] In addition, the preparation method designed by the present invention can also greatly improve the production efficiency of positive electrode materials, reduce production costs, and is more suitable for actual production needs. Specifically, first, the present invention uses an organic carbon source and a first raw material for solid-phase mixing and then combines a sintering process to obtain an intermediate with in-situ carbon coating, regulates the carbon coating morphology, and can improve the tightness and uniformity of the carbon material coating, ensure sufficient graphitization of the carbon material, thereby improving the conductivity of the positive electrode material, and the solid-phase mixing process used replaces the wet mixing process of the prior art, further optimizes the process operation, reduces production costs, and omits the subsequent drying process required for the wet mixing process, fundamentally solving the drying (especially spray drying) required for the subsequent wet mixing process on the organic carbon source during the mixing process. Influence, at the same time, the solid-phase mixing process combined with the selection of a low-cost organic carbon source can effectively reduce production costs and greatly improve production efficiency, so that the surface-coated carbon layer of the intermediate with in-situ carbon coating is coated with a specific morphology, and can isolate the sodium-containing compounds inside the carbon coating from the operating environment. The contact with water reduces the moisture sensitivity of the raw material, thereby improving the cyclic stability of the material; secondly, the intermediate with in-situ carbon coating is mixed with the second raw material for a second solid phase mixing to improve the uniformity of the mixing of the intermediate with in-situ carbon coating and the second raw material, and the added antioxidant can inhibit the oxidation of the raw material mixing process and improve the stability of the material; furthermore, the mixed precursor material is pressed and sintered in a combined process, which can not only regulate the form and morphology of the carbon coating of the obtained sodium positive electrode material, but also ensure the sufficient contact and sufficient reaction between the intermediate with in-situ carbon coating and the second raw material, reduce the atomic diffusion barrier in the precursor material, thereby improving the yield and product consistency of the obtained sodium positive electrode material, so as to improve the performance of the sodium positive electrode material; in addition, the pressing and sintering process adopted can also improve the bonding degree of the precursor particles, as well as effectively reduce the specific surface area of the carbon-coated positive electrode material and improve the compaction density of the obtained material.
[0047] Preferably, in step (1), the first raw material comprises sodium sulfate.
[0048] Preferably, the sodium sulfate includes any one of anhydrous sodium sulfate or sodium sulfate monohydrate.
[0049] Preferably, in step (1), the first raw material is also pretreated before the first solid-phase mixing.
[0050] Preferably, the specific process of pre-treating the first raw material includes: performing a first drying on the first raw material, and then performing a first crushing to obtain the pre-treated first raw material.
[0051] The present invention provides a pretreatment process for drying and crushing the first raw material, wherein the water content in the first raw material is reduced by drying, thereby reducing the water content in the obtained positive electrode material, and further improving the stability of the obtained sodium battery positive electrode material; and the crushing process is intended to reduce the particle size of the first raw material, thereby increasing the reaction activity of the first raw material and promoting sufficient reaction between the materials.
[0052] Preferably, the first drying temperature is 200-350°C, for example, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C or 350°C.
[0053] Preferably, the first drying time is 1-15 h, for example, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h or 15 h.
[0054] Preferably, a particle size D50 of the first raw material after the first crushing is less than 1 μm, for example, 1 μm, 0.9 μm, 0.8 μm, 0.7 μm, 0.6 μm or 0.5 μm.
[0055] In the present invention, there is no specific limitation on the first crushing method, including but not limited to mechanical ball milling or air flow milling, etc., and those skilled in the art can select it according to needs.
[0056] Preferably, the first crushing is performed in nitrogen and / or inert gas.
[0057] Preferably, the organic carbon source in step (1) comprises any one of glucose, ascorbic acid, citric acid, tea polyphenols or starch, or a combination of at least two thereof.
[0058] Preferably, in step (1), the mass ratio of the first raw material to the organic carbon source is (50-95):(5-50), wherein the selection range of the first raw material is "50-95", for example, 50, 55, 60, 65, 70, 75, 80, 85, 90 or 95, etc.; the selection range of the organic carbon source is "5-50", for example, 5, 10, 15, 20, 25, 30, 35, 40, 45 or 50, etc.
[0059] The present invention regulates the mass ratio of the first raw material and the organic carbon source during a solid-phase mixing process, thereby ensuring effective coating of the first raw material. At the same time, the amount of the organic carbon source added is controlled to avoid excessive thickness of the carbon layer coating, which hinders the subsequent mixing effect with the second raw material and thus affects the electrochemical properties of the material.
[0060] Preferably, before the first solid phase mixing in step (1), the first raw material and the organic carbon source are first premixed.
[0061] In the present invention, there is no specific limitation on the method of the primary solid phase mixing, including but not limited to air flow milling, rolling ball milling, planetary ball milling or vibration ball milling, etc. Those skilled in the art can select according to their needs.
[0062] Preferably, the sintering temperature in step (1) is 500-800°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C.
[0063] The present invention regulates the sintering temperature, performs in-situ carbon coating on the first raw material at a high temperature, and improves the degree of graphitization of the organic carbon material while avoiding decomposition of the first raw material, thereby ensuring sufficient graphitization of the carbon material, and further improving the conductivity of the obtained sodium positive electrode material. The present invention adopts high-temperature sintering in the mixing process of the first raw material and the organic carbon source to obtain an intermediate with in-situ carbon coating, and then mixes it with the second raw material. Compared with the process of sintering after mixing the sodium source, carbon source and iron source commonly used in the prior art, it can ensure sufficient graphitization of the carbon material while avoiding the decomposition of the iron-based sodium positive electrode material during the high-temperature sintering process, thereby improving the product consistency of the obtained sodium-based positive electrode material.
[0064] Preferably, the sintering time in step (1) is 4-10 h, for example, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0065] Preferably, the sintering atmosphere in step (1) is a nitrogen atmosphere and / or an inert atmosphere.
[0066] Preferably, in step (2), the second raw material comprises ferrous sulfate.
[0067] Preferably, the ferrous sulfate comprises anhydrous ferrous sulfate and / or ferrous sulfate hydrate.
[0068] Preferably, the hydrate of ferrous sulfate includes any one of ferrous sulfate heptahydrate, ferrous sulfate tetrahydrate or ferrous sulfate monohydrate.
[0069] Preferably, in step (2), the second raw material is also pretreated before the secondary solid phase mixing.
[0070] Preferably, the specific process of pre-treating the second raw material includes: performing a second drying on the second raw material, and then performing a second crushing to obtain the pre-treated second raw material.
[0071] The present invention performs a pretreatment process of drying and crushing the second raw material before secondary solid phase mixing, reduces the water content of the positive electrode material through the drying process, thereby improving the stability of the obtained positive electrode material, and reduces the particle size of the second raw material particles through the crushing process, thereby improving the reaction activity of the second raw material and promoting sufficient reaction between the materials.
[0072] Preferably, the second drying temperature is 200-350°C, for example, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C or 350°C.
[0073] Preferably, the second drying time is 1-15 h, for example, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h or 15 h.
[0074] Preferably, the particle size D50 of the second raw material after the second crushing is less than 1 μm, for example, 1 μm, 0.9 μm, 0.8 μm, 0.7 μm, 0.6 μm or 0.5 μm.
[0075] Preferably, the second crushing is performed in nitrogen and / or inert gas.
[0076] In the present invention, there is no specific limitation on the first crushing method, including but not limited to mechanical ball milling or air flow milling, etc., and those skilled in the art can select it according to needs.
[0077] Preferably, the molar ratio of the intermediate with in-situ carbon coating in step (2) to the second raw material is 1:(1-2), for example 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, etc.
[0078] The present invention provides a mass ratio of an intermediate with in-situ carbon coating to a second raw material, aiming to obtain sodium ferrous sulfate with different sodium-iron ratios and screen out sodium ferrous sulfate with better capacity and stability.
[0079] Preferably, the antioxidant is added in an amount of 0.01-10wt% of the mass of the second raw material, for example 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt% etc.
[0080] The invention regulates the amount of antioxidant added to ensure that the material is not oxidized while reducing the carbon content, increasing the compaction density of the obtained sodium positive electrode material and reducing its specific surface area.
[0081] Preferably, the antioxidant comprises any one of ascorbic acid, citric acid or tea polyphenols, or a combination of at least two thereof.
[0082] Preferably, before the secondary solid phase mixing in step (2), the intermediate with in-situ carbon coating, the second raw material and the antioxidant are subjected to a second premixing.
[0083] In the present invention, there is no specific limitation on the method of secondary solid phase mixing, including but not limited to air flow milling, rolling ball milling, planetary ball milling or vibration ball milling, etc. Those skilled in the art can select according to their needs.
[0084] Preferably, the specific process of pressing and sintering in step (3) includes: pressing the precursor material first and then sintering it, or pressing and sintering the precursor material at the same time.
[0085] In the present invention, the precursor material is pressed and sintered simultaneously, that is, the precursor material is subjected to a hot pressing and sintering process.
[0086] Preferably, the pressing pressure is 50-500 MPa, for example, 50 MPa, 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa or 500 MPa.
[0087] The present invention regulates the pressure of pressing the precursor material. On the one hand, it improves the bonding degree of the precursor particles, reduces the specific surface area of the obtained positive electrode material, increases the compaction density of the material, and reduces the atomic diffusion barrier of the precursor material, thereby improving the yield and product consistency of the positive electrode material. On the other hand, it avoids excessive pressing pressure, which leads to excessive hardness of the material, making subsequent crushing difficult, thereby affecting the performance of the sodium positive electrode material. In addition, the regulation of pressing pressure is also conducive to the preparation of positive electrode materials with two coating forms: partial carbon coating and full carbon coating.
[0088] Preferably, the sintering temperature is 280-380°C, for example, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C or 380°C.
[0089] The present invention regulates the sintering temperature of the precursor material and successfully prepares a sodium cathode material with better product consistency, while avoiding decomposition of the obtained sodium ferrous sulfate matrix material due to excessively high temperature, thereby affecting the yield and purity of the sodium cathode material.
[0090] Preferably, when the precursor material is pressed first and then sintered, the pressing time is 1-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, etc.; the sintering time is 15-25 h, for example, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h or 25 h, etc.
[0091] Preferably, when the precursor material is pressed and sintered simultaneously, the pressing and sintering are performed simultaneously for 10-15 hours, such as 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0092] Preferably, the product obtained after pressing and sintering in step (3) is also crushed and sieved.
[0093] As a preferred technical solution of the present invention, the method for preparing the sodium positive electrode material comprises the following steps:
[0094] S1. The first raw material is placed at 200-350° C. for 1-15 hours for the first drying, and then the first dried product is first crushed under nitrogen and / or inert gas protection, the particle size D50 of the first raw material after the first crushing is less than 1 μm, to obtain a pretreated first raw material;
[0095] The second raw material is placed at 200-350° C. for 1-15 hours for second drying, and then the product after the second drying is second crushed under the protection of nitrogen and / or inert gas, wherein the particle size D50 of the second raw material after the second crushing is less than 1 μm, thereby obtaining a pretreated second raw material;
[0096] S2. Premixing the pretreated first raw material and the organic carbon source in a mass ratio of (50-95):(5-50), then performing solid phase mixing again, and then sintering at 500-800° C. for 4-10 h under a nitrogen atmosphere and / or an inert atmosphere to obtain an intermediate having an in-situ carbon coating;
[0097] S3. Premixing the intermediate with in-situ carbon coating, the pretreated second raw material and the antioxidant first, and then performing secondary solid phase mixing, wherein the molar ratio of the intermediate with in-situ carbon coating to the pretreated second raw material is 1:(1-2), and the amount of the antioxidant added is 0.01-10wt% of the mass of the second raw material, to obtain a precursor material;
[0098] S4. The precursor material is pressed and sintered at a pressing pressure of 50-500MPa and a sintering temperature of 280-380°C. The specific process of pressing and sintering includes: pressing the precursor material for 1-10min and then sintering it for 15-25h, or pressing and sintering the precursor material for 10-15h at the same time, and then crushing and sieving the product obtained after pressing and sintering to obtain the sodium positive electrode material.
[0099] In a third aspect, the present invention provides a positive electrode plate, which includes the sodium-based positive electrode material described in the first aspect, or the sodium-based positive electrode material prepared by the preparation method described in the second aspect.
[0100] In a fourth aspect, the present invention provides a sodium ion battery, comprising the positive electrode plate described in the third aspect.
[0101] The sodium ion battery formed by the sodium electric positive electrode material with excellent performance of the present invention has excellent cycle stability and good rate performance.
[0102] Compared with the prior art, the present invention has at least the following beneficial effects:
[0103] (1) The sodium positive electrode material provided by the present invention is coated with a carbon layer on the surface of the base material, which can improve the stability of the sodium positive electrode material and improve the conductivity of the material itself, and further control the form of carbon coating. Through the mutual coordination of partial carbon coating and full carbon coating on the base material, the partial coating is further regulated to adopt a specific form of sheet and / or point. It can ensure that the sodium positive electrode material has excellent conductivity and stability, and can also promote the effective transmission of sodium ions in the material and improve the deintercalation of sodium ions inside the material, so that the sodium positive electrode material can have multiple advantages of excellent capacity performance and stable cycle performance.
[0104] (2) The present invention designs the mixing sequence and mixing process of the raw materials in combination with the sintering process. On the one hand, it is possible to regulate the carbon coating form and morphology in the sodium positive electrode material to ensure that the obtained sodium positive electrode material has both full carbon coating and partial carbon coating, and to regulate the morphology of the partial carbon coating, which is beneficial to improve the deintercalation of sodium ions in the sodium positive electrode material while improving the conductivity of the sodium positive electrode material; on the other hand, the designed preparation process first obtains an intermediate with in-situ carbon coating by solid-phase mixing of the first raw material and the organic carbon source once, regulates the carbon coating morphology, and reduces the moisture sensitivity of the intermediate to ensure sufficient graphitization of the carbon, and then, by a secondary solid-phase mixing of the intermediate with in-situ carbon coating with the second raw material and the antioxidant and then pressing and sintering process, while regulating the carbon coating form and morphology of the obtained sodium positive electrode material, it is also possible to improve the sufficient reaction of the intermediate with in-situ carbon coating and the second raw material, reduce the specific surface area of the obtained positive electrode material and increase the compaction density of the material, thereby obtaining a sodium positive electrode material with excellent performance. In addition, the preparation method designed by the present invention can also greatly improve the production efficiency of sodium battery positive electrode materials and reduce production costs, and is more suitable for actual production needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0105] Figure 1 Schematic diagram of the gap distance between carbon layers in the present invention.
[0106] Among them, 1, the surface of the base material; 2, the carbon layer; d, the gap distance between the carbon layers.
[0107] Figure 2 This is a scanning electron microscope image of the in-situ carbon-coated sodium sulfate prepared in Example 1.
[0108] Figure 3 yes Figure 2 Energy dispersive X-ray spectrum of carbon element corresponding to the scanning electron microscope image.
[0109] Figure 4 This is the X-ray diffraction pattern of the sodium positive electrode material prepared in Example 1.
[0110] Figure 5 This is a scanning electron microscope image of the sodium positive electrode material prepared in Example 1 at a low magnification.
[0111] Figure 6 yes Figure 5 Energy dispersive X-ray spectrum of carbon element corresponding to the scanning electron microscope image.
[0112] Figure 7 This is a scanning electron microscope image of the sodium positive electrode material prepared in Example 1 at a high magnification.
[0113] Figure 8 It is a charge and discharge curve diagram of the sodium ion battery provided in Application Example 1 and Application Examples 4-7 at 0.1C.
[0114] Fig. 9 It is a charge and discharge curve diagram of the sodium ion battery provided in Application Example 1 and Application Examples 8-9 at 0.1C.
[0115] Fig.10 It is a charge and discharge curve diagram of the sodium ion battery provided in Application Example 1 and Application Example 14 at 0.1C.
[0116] Fig.11 It is a charge and discharge curve diagram of the sodium ion battery provided in Application Example 1, Application Example 22 and Comparative Application Example 1 at 0.1C. DETAILED DESCRIPTION
[0117] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0118] The following embodiments involve the gap distance between carbon layers, and the schematic diagram thereof is shown as follows: Figure 1As shown, the gap distance d between the carbon layers specifically refers to the distance between the partially covered carbon layers 2 and the partially covered carbon layers 2 on the surface 1 of the base material.
[0119] The morphology of the sodium cathode material involved in the following embodiments and the parameters related to its morphology and size are obtained by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS), wherein the thickness of the carbon layer is obtained based on the cross-sectional scanning electron microscopy image of the obtained sodium cathode material; the diameter and gap distance of the point-shaped and sheet-shaped carbon layer: the edges of the point-shaped carbon layer and the sheet-shaped carbon layer coated on the surface of the matrix material in the sodium cathode material are determined by SEM combined with EDS, and obtained by direct measurement combined with statistics; the size of the primary particles and secondary particles: obtained by direct measurement combined with statistics through SEM.
[0120] The pressing mold used in the following examples is a cylinder with a diameter of 60 cm, a wall thickness of 10 cm and a height of 40 cm.
[0121] Example 1
[0122] This embodiment provides a method for preparing a carbon-coated sodium ferrous sulfate positive electrode material, comprising the following steps:
[0123] S1. Place anhydrous sodium sulfate at 200° C. for a first drying for 10 hours, and then crush the anhydrous sodium sulfate after the first drying under nitrogen protection with a nitrogen gas flow at a gas flow pressure of 1.5 MPa for 10 minutes until the particle size D50 of the anhydrous sodium sulfate is 0.8 μm, thereby obtaining pretreated sodium sulfate for standby use.
[0124] The ferrous sulfate heptahydrate was placed at 350° C. for a second drying for 10 hours to obtain anhydrous ferrous sulfate. Then, the obtained anhydrous ferrous sulfate was crushed under nitrogen protection with a nitrogen gas flow with a gas flow pressure of 1.5 MPa for 10 minutes until the particle size D50 of the anhydrous ferrous sulfate was 0.8 μm, and the pretreated ferrous sulfate was obtained for use.
[0125] S2. Premix 4000 g of the pretreated sodium sulfate obtained in step S1 with 1000 g of glucose in a high-speed mixer, then stir and ball-mill at a speed of 400 rpm for 6 hours, and then sinter the product after stirring and ball-milling at 600° C. for 8 hours. The sintering is carried out under a nitrogen atmosphere to obtain in-situ carbon-coated sodium sulfate.
[0126] S3. Premix 2085 g of the in-situ carbon-coated sodium sulfate obtained in step S2, 3028 g of the pretreated ferrous sulfate obtained in step S1, and 152 g of ascorbic acid in a high-speed mixer, and then mill them in a planetary ball mill at 500 rpm for 6 h to obtain a precursor material.
[0127] S4. Load the precursor material obtained in step S3 into a hot pressing mold, place the material together with the mold in a hot pressing furnace, pressurize it to 100 MPa, and heat it to 350°C to perform hot pressing sintering on the precursor material for 12 hours, then cool it to 150°C and take out the material. Then, crush the taken out material, and sieve it with a sieve with a mesh size of 325 to obtain a sodium positive electrode material.
[0128] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72 (SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-50nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-30nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on the partial surface of sodium ferrous sulfate is 30:70; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in a point shape, positive electrode materials that are all carbon-coated in a sheet shape, and positive electrode materials that are both carbon-coated in a point shape and carbon-coated in a sheet shape in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point shape ranges from 1 to 65 nm, and the gap distance between the carbon layers in the point shape ranges from 1 to 70 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-300nm, and the gap distance between the flake carbon layers is in the range of 1-90nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-65nm, the diameter of the flake carbon coating is in the range of 100-300nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the carbon content of the sodium positive electrode material is 0.1%. The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 95wt%, and the content of free carbon is 5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-600nm, the average size is 361nm, the size range of the secondary particles is 0.01-50μm, the average size is 26μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 65wt%, and the content of the secondary particles is 35wt%.
[0129] Example 2
[0130] This embodiment provides a method for preparing a carbon-coated sodium ferrous sulfate positive electrode material, comprising the following steps:
[0131] S1. Sodium sulfate decahydrate is placed at 350° C. for a first drying for 2 hours to obtain anhydrous sodium sulfate. Then, the obtained anhydrous sodium sulfate is crushed under argon protection with an argon gas flow with a gas flow pressure of 1 MPa for 10 minutes until the particle size D50 of the anhydrous sodium sulfate is 1 μm, thereby obtaining pretreated sodium sulfate for standby use.
[0132] The anhydrous ferrous sulfate was placed at 200° C. for a second drying for 5 hours, and then the anhydrous ferrous sulfate after the second drying was crushed under argon protection with an argon gas flow with a gas flow pressure of 1 MPa for 10 minutes until the particle size D50 of the anhydrous ferrous sulfate was 1 μm, thereby obtaining the pretreated ferrous sulfate for use.
[0133] S2. Premix 4000 g of the pretreated sodium sulfate obtained in step S1 with 1000 g of starch in a high-speed mixer, then vibrate-mill at a rotation speed of 400 rpm for 3 hours, and then sinter the product after vibration ball milling at 500° C. for 10 hours. The sintering is carried out under an argon atmosphere to obtain in-situ carbon-coated sodium sulfate.
[0134] S3. Premix 2085 g of the in-situ carbon-coated sodium sulfate obtained in step S2, 2500 g of the pretreated ferrous sulfate obtained in step S1, and 84 g of citric acid in a high-speed mixer, and then mill in a planetary ball mill at 500 rpm for 10 h to obtain a precursor material.
[0135] S4. Load the precursor material obtained in step S3 into a hot pressing mold, place the material together with the mold in a hot pressing furnace, pressurize it to 150 MPa, and heat it to 300°C to perform hot pressing sintering on the precursor material for 15 hours, then cool it to 120°C to take out the material, then crush the taken out material, and then sieve it with a sieve with a mesh size of 325 to obtain a sodium positive electrode material.
[0136] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.6 Fe 1.7(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 6wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-48nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-35nm; in the sodium positive electrode material, the carbon layer coated on the sulfuric acid The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with a carbon layer on a partial surface of sodium ferrous sulfate is 29:71; the positive electrode material partially coated with a carbon layer includes positive electrode materials that are all carbon-coated in a point-like manner, sodium-based positive electrode materials that are all carbon-coated in a sheet-like manner, and positive electrode materials that are both carbon-coated in a point-like manner and carbon-coated in a sheet-like manner, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point-like manner ranges from 1 to 70 nm, and the gap distance between the carbon layers in a point-like manner ranges from 1 to 65 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-400nm, the gap distance between the flake carbon layers is in the range of 1-80nm, in the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-70nm, the diameter of the flake carbon coating is in the range of 100-350nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-70nm; in the sodium positive electrode material, free carbon is also included, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 94wt%, and the free carbon content is 6wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-550nm, the average size is 352nm, the size range of the secondary particles is 0.01-70μm, the average size is 29μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 62wt%, and the content of the secondary particles is 38wt%.
[0137] Example 3
[0138] This embodiment provides a method for preparing a carbon-coated sodium ferrous sulfate positive electrode material, comprising the following steps:
[0139] S1. Place anhydrous sodium sulfate at 300° C. for a first drying for 5 hours, and then crush the anhydrous sodium sulfate after the first drying under nitrogen protection with a nitrogen gas flow with a gas flow pressure of 2 MPa for 5 minutes until the particle size D50 of the anhydrous sodium sulfate is 0.6 μm, thereby obtaining pretreated sodium sulfate for standby use.
[0140] The ferrous sulfate tetrahydrate was placed at 300° C. for a second drying for 15 hours to obtain anhydrous ferrous sulfate. Then, the obtained anhydrous ferrous sulfate was crushed under nitrogen protection with a nitrogen gas flow with a gas flow pressure of 2 MPa for 5 minutes until the particle size D50 of the anhydrous ferrous sulfate was 0.6 μm, and the pretreated ferrous sulfate was obtained for use.
[0141] S2. Premix 4000 g of the pretreated sodium sulfate obtained in step S1 with 1000 g of tea polyphenols in a high-speed mixer, then roll-mill at a rotation speed of 600 rpm for 5 hours, and then sinter the product after rolling ball milling at 800°C for 5 hours. The sintering is carried out under a nitrogen atmosphere to obtain in-situ carbon-coated sodium sulfate.
[0142] S3. Premix 2085 g of the in-situ carbon-coated sodium sulfate obtained in step S2, 3800 g of the pretreated ferrous sulfate obtained in step S1, and 308 g of citric acid in a high-speed mixer, and then mill in a planetary ball mill at 600 rpm for 5 h to obtain a precursor material.
[0143] S4. Load the precursor material obtained in step S3 into a hot pressing mold, place the material together with the mold in a hot pressing furnace, pressurize it to 120 MPa, and heat it to 360°C to perform hot pressing sintering on the precursor material for 10 hours, then cool it to 100°C to take out the material, then crush the taken out material, and then sieve it with a sieve with a mesh size of 325 to obtain a sodium positive electrode material.
[0144] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.5 Fe 1.75(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 4wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-40nm, and the thickness of the carbon layer coated on the portion of the surface of sodium ferrous sulfate being in the range of 1-25nm; in the sodium positive electrode material, the carbon layer is entirely coated on the surface of the sodium ferrous sulfate. The mass ratio of the positive electrode material coated on sodium ferrous sulfate to the positive electrode material partially coated on sodium ferrous sulfate with a carbon layer is 20:80; the positive electrode material partially coated with a carbon layer includes positive electrode materials that are all carbon-coated in a point shape, positive electrode materials that are all carbon-coated in a sheet shape, and positive electrode materials in which both carbon-coating in a point shape and carbon-coating in a sheet shape exist in any proportion, wherein the diameter of the carbon layer in the positive electrode material coated only in a point shape is in the range of 1-60nm, the gap distance between the carbon layers in a point shape is in the range of 1-80nm, and the positive electrode material coated only in a point shape is in the range of 1-80nm. The diameter of the carbon layer of the positive electrode material coated with flaky carbon is in the range of 100-280nm, and the gap distance between the flaky carbon layers is in the range of 1-110nm. In the positive electrode material in which flaky carbon coating and point-like carbon coating exist at the same time, the diameter of the point-like carbon coating is in the range of 1-55nm, the diameter of the flaky carbon coating is in the range of 100-250nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-100nm; the sodium positive electrode material also includes free carbon, and the total carbon content of the sodium positive electrode material is 1.0%. The content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 97wt%, and the content of free carbon is 3wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-700nm, the average size is 462nm, the size range of the secondary particles is 0.01-60μm, the average size is 38μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 63wt%, and the content of the secondary particles is 37wt%.
[0145] Example 4
[0146] The difference between this embodiment and embodiment 1 is that in step S2 of the preparation method provided in this embodiment, the mass of pretreated sodium sulfate added is 4750 g, the mass of glucose is 250 g, and the mass of in-situ carbon-coated sodium sulfate added in step S3 is 2022 g. The remaining process parameters are the same as those in embodiment 1.
[0147] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 1wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 2-20nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-15nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with a carbon layer on a partial surface of sodium ferrous sulfate is 7:93; the positive electrode material partially coated with a carbon layer includes positive electrode materials that are all carbon-coated in a point-like manner, sodium-based positive electrode materials that are all carbon-coated in a sheet-like manner, and positive electrode materials that are both carbon-coated in a point-like manner and carbon-coated in a sheet-like manner, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point-like manner ranges from 1 to 25 nm, and the gap distance between the carbon layers in a point-like manner ranges from 1 to 75 nm. , the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-200nm, and the gap distance between the flake carbon layers is in the range of 1-200nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-25nm, the diameter of the flake carbon coating is in the range of 100-200nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-180nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 97wt%, and the content of free carbon is 3wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-700nm, the average size is 537nm, the size range of the secondary particles is 0.01-70μm, the average size is 45μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 60wt%, and the content of the secondary particles is 40wt%.
[0148] Example 5
[0149] The difference between this embodiment and embodiment 1 is that in step S2 of the preparation method provided in this embodiment, the mass of pretreated sodium sulfate added is 4500 g, the mass of glucose is 500 g, and the mass of in-situ carbon-coated sodium sulfate added in step S3 is 2043 g. The remaining process parameters are the same as those in embodiment 1.
[0150] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 2.5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 2-30nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-20nm; in the sodium positive electrode material, the carbon layer coated on The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 15:85; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium positive electrode materials that are all carbon-coated in flakes, and positive electrode materials that are both carbon-coated in dots and carbon-coated in flakes in any proportion, wherein the diameter of the carbon layer in the positive electrode material coated only in dots is in the range of 1-32nm, and the gap distance between the carbon layers in dots is in the range of 1-71nm m, the diameter of the carbon layer of the positive electrode material with only flaky carbon coating is in the range of 100-260nm, and the gap distance between the flaky carbon layers is in the range of 1-200nm. In the positive electrode material with both flaky carbon coating and point-like carbon coating, the diameter of the point-like carbon coating is in the range of 1-32nm, the diameter of the flaky carbon coating is in the range of 100-260nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-120nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 96wt%, and the content of free carbon is 4wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-600nm, the average size is 486nm, the size range of the secondary particles is 0.01-67μm, the average size is 43μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 67wt%, and the content of the secondary particles is 33wt%.
[0151] Example 6
[0152] The difference between this embodiment and embodiment 1 is that in step S2 of the preparation method provided in this embodiment, the mass of pretreated sodium sulfate added is 3500 g, the mass of glucose is 1500 g, and the mass of in-situ carbon-coated sodium sulfate added in step S3 is 2130 g. The other process parameters are the same as those in embodiment 1.
[0153] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 7wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 1-40nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-38nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on the partial surface of sodium ferrous sulfate is 41:59; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in a point shape, positive electrode materials that are all carbon-coated in a sheet shape, and positive electrode materials that are both carbon-coated in a point shape and carbon-coated in a sheet shape in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point shape ranges from 1 to 75 nm, and the gap distance between the carbon layers in the point shape ranges from 1 to 55 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-400nm, and the gap distance between the flake carbon layers is in the range of 1-70nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-75nm, the diameter of the flake carbon coating is in the range of 100-400nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-65nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 92wt%, and the content of free carbon is 8wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-450nm, the average size is 310nm, the size range of the secondary particles is 0.01-40μm, the average size is 21μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 70wt%, and the content of the secondary particles is 30wt%.
[0154] Example 7
[0155] The difference between this embodiment and embodiment 1 is that in step S2 of the preparation method provided in this embodiment, the mass of pretreated sodium sulfate added is 3000 g, the mass of glucose is 2000 g, and the mass of in-situ carbon-coated sodium sulfate added in step S3 is 2229 g. The remaining process parameters are the same as those in embodiment 1.
[0156] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 10wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 1-45nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-41nm; in the sodium positive electrode material, the carbon layer coated on The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 45:55; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium positive electrode materials that are all carbon-coated in flakes, and positive electrode materials that are both carbon-coated in dots and carbon-coated in flakes in any proportion, wherein the diameter of the carbon layer in the positive electrode material coated only in dots is in the range of 1-80nm, and the gap distance between the carbon layers in dots is in the range of 1-60nm m, the diameter of the carbon layer of the positive electrode material with only flaky carbon coating is in the range of 100-450nm, and the gap distance between the flaky carbon layers is in the range of 1-60nm. In the positive electrode material with both flaky carbon coating and point-like carbon coating, the diameter of the point-like carbon coating is in the range of 1-55nm, the diameter of the flaky carbon coating is in the range of 100-450nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-60nm; free carbon is also included in the sodium positive electrode material, and the carbon content of the sodium positive electrode material is 1.5-1.0. The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 90wt%, and the content of free carbon is 10wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-400nm, the average size is 300nm, the size range of the secondary particles is 0.01-35μm, the average size is 18μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 75wt%, and the content of the secondary particles is 25wt%.
[0157] Example 8
[0158] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the hot pressing sintering temperature of step S4 is 330° C. and the hot pressing sintering time is 15 hours. The other process parameters are the same as those in embodiment 1.
[0159] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-50nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-30nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on the partial surface of sodium ferrous sulfate is 30:70; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in a point shape, positive electrode materials that are all carbon-coated in a sheet shape, and positive electrode materials that are both carbon-coated in a point shape and carbon-coated in a sheet shape in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point shape ranges from 1 to 65 nm, and the gap distance between the carbon layers in the point shape ranges from 1 to 70 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-300nm, and the gap distance between the flake carbon layers is in the range of 1-90nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-65nm, the diameter of the flake carbon coating is in the range of 100-300nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the carbon content of the sodium positive electrode material is 0.1%. The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 95wt%, and the content of free carbon is 5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-500nm, the average size is 280nm, the size range of the secondary particles is 0.01-35μm, the average size is 15μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 75wt%, and the content of the secondary particles is 25wt%.
[0160] Example 9
[0161] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, in step S4, the mold containing the material is pressed at 300 MPa for 3 minutes and then sintered at 350° C. for 20 hours. The other process parameters are the same as those in embodiment 1.
[0162] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-50nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-30nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on the partial surface of sodium ferrous sulfate is 30:70; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in a point shape, positive electrode materials that are all carbon-coated in a sheet shape, and positive electrode materials that are both carbon-coated in a point shape and carbon-coated in a sheet shape in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point shape ranges from 1 to 65 nm, and the gap distance between the carbon layers in the point shape ranges from 1 to 70 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-300nm, and the gap distance between the flake carbon layers is in the range of 1-90nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-65nm, the diameter of the flake carbon coating is in the range of 100-300nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the carbon content of the sodium positive electrode material is 0.1%. The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 95wt%, and the content of free carbon is 5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-400nm, the average size is 220nm, the size range of the secondary particles is 0.01-35μm, the average size is 12μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 78wt%, and the content of the secondary particles is 22wt%.
[0163] Example 10
[0164] The difference between this embodiment and embodiment 1 is that the preparation method provided in this embodiment omits the pretreatment process of anhydrous sodium sulfate in step S1. The other process parameters are the same as those in embodiment 1.
[0165] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-55nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-40nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with a carbon layer on a partial surface of sodium ferrous sulfate is 35:65; the positive electrode material partially coated with a carbon layer includes positive electrode materials that are all carbon-coated in a point-like manner, sodium-based positive electrode materials that are all carbon-coated in a sheet-like manner, and positive electrode materials that are both carbon-coated in a point-like manner and carbon-coated in a sheet-like manner, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point-like manner ranges from 1 to 80 nm, and the gap distance between the carbon layers in the point-like manner ranges from 1 to 70 nm. m, the diameter of the carbon layer of the positive electrode material with only flaky carbon coating is in the range of 100-310nm, and the gap distance between the flaky carbon layers is in the range of 1-90nm. In the positive electrode material with both flaky carbon coating and point-like carbon coating, the diameter of the point-like carbon coating is in the range of 1-80nm, the diameter of the flaky carbon coating is in the range of 100-310nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the carbon content of the sodium positive electrode material is 1.0%. The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 94wt%, and the content of free carbon is 6wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-1100nm, the average size is 530nm, the size range of the secondary particles is 0.01-60μm, the average size is 45μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 68wt%, and the content of the secondary particles is 32wt%.
[0166] Embodiment 11
[0167] The difference between this embodiment and embodiment 1 is that the preparation method provided in this embodiment omits the pretreatment process of ferrous sulfate heptahydrate in step S1. The other process parameters are the same as those in embodiment 1.
[0168] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-50nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-30nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on the partial surface of sodium ferrous sulfate is 30:70; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in a point shape, positive electrode materials that are all carbon-coated in a sheet shape, and positive electrode materials that are both carbon-coated in a point shape and carbon-coated in a sheet shape in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point shape ranges from 1 to 65 nm, and the gap distance between the carbon layers in the point shape ranges from 1 to 70 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-300nm, and the gap distance between the flake carbon layers is in the range of 1-90nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-65nm, the diameter of the flake carbon coating is in the range of 100-300nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the carbon content of the sodium positive electrode material is 0.1%. The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 95wt%, and the free carbon content is 5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-1080nm, the average size is 480nm, the size range of the secondary particles is 0.01-60μm, the average size is 34μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 62wt%, and the content of the secondary particles is 38wt%.
[0169] Example 12
[0170] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the mass of sodium sulfate after pretreatment in step S2 is 4000 g, and the mass of glucose is 100 g. The other process parameters are the same as those in embodiment 1.
[0171] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 0.4wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 0.5-10nm, and the thickness of the carbon layer coated on the portion of the surface of sodium ferrous sulfate being in the range of 0.5-8nm; in the sodium positive electrode material, the carbon layer coated on the entire surface of sodium ferrous sulfate is in the range of 0.5-10nm, and the carbon layer coated on the portion of the surface of sodium ferrous sulfate is in the range of 0.5-8nm; The mass ratio of the positive electrode material coated on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 3:97; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium-based positive electrode materials that are all carbon-coated in flakes, and positive electrode materials that are both carbon-coated in dots and carbon-coated in flakes in any proportion, wherein the diameter of the carbon layer in the positive electrode material coated only in dots is in the range of 0.5-15 nm, and the gap distance between the carbon layers in the dots is in the range of 1-11 2nm, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-150nm, and the gap distance between the flake carbon layers is in the range of 1-230nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 0.5-15nm, the diameter of the flake carbon coating is in the range of 100-150nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-210nm; free carbon is also included in the sodium positive electrode material, and the sodium positive electrode material The total carbon content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 99wt%, and the free carbon content is 1wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-850nm, the average size is 653nm, the size range of the secondary particles is 0.01-85μm, the average size is 53μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 65wt%, and the content of the secondary particles is 35wt%.
[0172] Embodiment 13
[0173] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the mass of sodium sulfate after pretreatment in step S2 is 2000 g, and the mass of glucose is 2500 g. The remaining process parameters are the same as those in embodiment 1.
[0174] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 10wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-58nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 5-55nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on the partial surface of sodium ferrous sulfate is 52:48; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in a point shape, positive electrode materials that are all carbon-coated in a sheet shape, and positive electrode materials that are both carbon-coated in a point shape and carbon-coated in a sheet shape in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point shape ranges from 10 to 80 nm, and the gap distance between the carbon layers in the point shape ranges from 1 to 58 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-480nm, and the gap distance between the flake carbon layers is in the range of 1-48nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 10-80nm, the diameter of the flake carbon coating is in the range of 100-480nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-46nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 84wt%, and the content of free carbon is 16wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-300nm, the average size is 246nm, the size range of the secondary particles is 0.01-30μm, the average size is 15μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 80wt%, and the content of the secondary particles is 20wt%.
[0175] Embodiment 14
[0176] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the sintering temperature in step S2 is 400° C. The other process parameters are the same as those in embodiment 1.
[0177] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 10-65nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 10-55nm; in the sodium positive electrode material, the carbon layer coated on The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 40:60; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium positive electrode materials that are all carbon-coated in flakes, and positive electrode materials that are both carbon-coated in dots and carbon-coated in flakes in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in dots ranges from 5 to 80 nm, and the gap distance between the carbon layers in dots ranges from 1 to 45 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-450nm, and the gap distance between the flake carbon layers is in the range of 1-60nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 5-80nm, the diameter of the flake carbon coating is in the range of 100-450nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-60nm; free carbon is also included in the sodium positive electrode material, and the total carbon content of the sodium positive electrode material is 1. The content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 95wt%, and the content of free carbon is 5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-1200nm, the average size is 523nm, the size range of the secondary particles is 0.01-863μm, the average size is 107μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 56wt%, and the content of the secondary particles is 44wt%.
[0178] Embodiment 15
[0179] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the sintering temperature in step S2 is 900° C. The other process parameters are the same as those in embodiment 1.
[0180] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-45nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-28nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on the partial surface of sodium ferrous sulfate is 40:60; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium positive electrode materials that are all carbon-coated in flakes, and positive electrode materials with both carbon-coated dots and carbon-coated flakes, wherein the diameter of the carbon layer in the positive electrode material coated with only carbon-coated dots is in the range of 1-70nm, and the gap distance between the carbon layers in the dots is in the range of 1-60nm. m, the diameter of the carbon layer of the positive electrode material with only flaky carbon coating is in the range of 100-400nm, and the gap distance between the flaky carbon layers is in the range of 1-73nm. In the positive electrode material with both flaky carbon coating and point-like carbon coating, the diameter of the point-like carbon coating is in the range of 1-70nm, the diameter of the flaky carbon coating is in the range of 100-400nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-73nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 85wt%, and the content of free carbon is 15wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-550nm, the average size is 345nm, the size range of the secondary particles is 0.01-46μm, the average size is 22μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 70wt%, and the content of the secondary particles is 30wt%.
[0181] Example 16
[0182] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the amount of ascorbic acid added in step S3 is 0.5 g. The other process parameters are the same as those in embodiment 1.
[0183] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-48nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-28nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with a carbon layer on a partial surface of sodium ferrous sulfate is 25:75; the positive electrode material partially coated with a carbon layer includes positive electrode materials that are all carbon-coated in a point-like manner, positive electrode materials that are all carbon-coated in a sheet-like manner, and positive electrode materials that are both carbon-coated in a point-like manner and carbon-coated in a sheet-like manner, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point-like manner ranges from 1 to 60 nm, and the gap distance between the carbon layers in the point-like manner ranges from 1 to 80 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-280nm, and the gap distance between the flake carbon layers is in the range of 1-92nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-60nm, the diameter of the flake carbon coating is in the range of 100-280nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-80nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 96wt%, and the content of free carbon is 4wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-620nm, the average size is 372nm, the size range of the secondary particles is 0.01-56μm, the average size is 30μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 65wt%, and the content of the secondary particles is 35wt%.
[0184] Embodiment 17
[0185] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the amount of ascorbic acid added in step S3 is 400 g. The other process parameters are the same as those in embodiment 1.
[0186] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 6wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-54nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-33nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with a carbon layer on a partial surface of sodium ferrous sulfate is 32:68; the positive electrode material partially coated with a carbon layer includes positive electrode materials that are all carbon-coated in a point-like manner, positive electrode materials that are all carbon-coated in a sheet-like manner, and positive electrode materials that are both carbon-coated in a point-like manner and carbon-coated in a sheet-like manner, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point-like manner ranges from 1 to 71 nm, and the gap distance between the carbon layers in a point-like manner ranges from 1 to 70 nm. m, the diameter of the carbon layer of the positive electrode material with only flaky carbon coating is in the range of 100-340nm, and the gap distance between the flaky carbon layers is in the range of 1-84nm. In the positive electrode material with both flaky carbon coating and point-like carbon coating, the diameter of the point-like carbon coating is in the range of 1-71nm, the diameter of the flaky carbon coating is in the range of 100-340nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-72nm; free carbon is also included in the sodium positive electrode material, and the carbon content of the sodium positive electrode material is 1.1%. The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 94wt%, and the content of free carbon is 6wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-570nm, the average size is 340nm, the size range of the secondary particles is 0.01-46μm, the average size is 24μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 68wt%, and the content of the secondary particles is 32wt%.
[0187] Embodiment 18
[0188] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the pressure of the pressurization in step S4 is 10 MPa. The other process parameters are the same as those in embodiment 1.
[0189] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-50nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-30nm; in the sodium positive electrode material, the carbon layer coated on The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 30:70; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium-based positive electrode materials that are all carbon-coated in flakes, and positive electrode materials with both carbon-coated dots and carbon-coated flakes in any proportion, wherein the diameter of the carbon layer in the positive electrode material coated with only carbon-coated dots is in the range of 1-65 nm, and the gap distance between the carbon-coated dots is in the range of 1-70 nm, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-300nm, and the gap distance between the flake carbon layers is in the range of 1-90nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-65nm, the diameter of the flake carbon coating is in the range of 100-300nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 95wt%, and the content of free carbon is 5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-500nm, the average size is 30nm, the size range of the secondary particles is 0.01-45μm, the average size is 24μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 75wt%, and the content of the secondary particles is 25wt%.
[0190] Embodiment 19
[0191] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the pressure of the pressurization in step S4 is 600 MPa. The other process parameters are the same as those in embodiment 1.
[0192] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-50nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-30nm; in the sodium positive electrode material, the carbon layer coated on the sulfur The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on the partial surface of sodium ferrous sulfate is 30:70; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in a point shape, positive electrode materials that are all carbon-coated in a sheet shape, and positive electrode materials that are both carbon-coated in a point shape and carbon-coated in a sheet shape in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point shape ranges from 1 to 65 nm, and the gap distance between the carbon layers in the point shape ranges from 1 to 70 nm. m, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-300nm, and the gap distance between the flake carbon layers is in the range of 1-90nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-65nm, the diameter of the flake carbon coating is in the range of 100-300nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the carbon content of the sodium positive electrode material is 0.1%. The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 95wt%, and the content of free carbon is 5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-900nm, the average size is 563nm, the size range of the secondary particles is 0.01-105μm, the average size is 58μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 45wt%, and the content of the secondary particles is 55wt%.
[0193] Embodiment 20
[0194] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the temperature of hot pressing sintering in step S4 is 200° C. The other process parameters are the same as those in embodiment 1.
[0195] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5.5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-52nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-32nm; in the sodium positive electrode material, the carbon layer coated on The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 32:68; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium positive electrode materials that are all carbon-coated in flakes, and positive electrode materials that are both carbon-coated in dots and carbon-coated in flakes in any proportion, wherein the diameter of the carbon layer in the positive electrode material coated only in dots is in the range of 1-68nm, and the gap distance between the carbon layers in dots is in the range of 1-70nm , the diameter of the carbon layer of the positive electrode material with only flaky carbon coating is in the range of 100-310nm, and the gap distance between the flaky carbon layers is in the range of 1-85nm. In the positive electrode material with both flaky carbon coating and point-like carbon coating, the diameter of the point-like carbon coating is in the range of 1-68nm, the diameter of the flaky carbon coating is in the range of 100-310nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-68nm; free carbon is also included in the sodium positive electrode material, and the total carbon content in the sodium positive electrode material is 1. The amount is 100wt%, the carbon content used for coating sodium ferrous sulfate is 94.5wt%, and the content of free carbon is 5.5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-430nm, the average size is 213nm, the size range of the secondary particles is 0.01-45μm, the average size is 23μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 72wt%, and the content of the secondary particles is 28wt%.
[0196] Embodiment 21
[0197] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the temperature of hot pressing sintering in step S4 is 400° C. The other process parameters are the same as those in embodiment 1.
[0198] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 4.9wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-48nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-29nm; in the sodium positive electrode material, the carbon layer coated on The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 29:71; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium positive electrode materials that are all carbon-coated in flakes, and positive electrode materials that are both carbon-coated in dots and carbon-coated in flakes in any proportion, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in dots ranges from 1 to 62 nm, and the gap distance between the carbon layers in dots ranges from 1 to 72 nm , the diameter of the carbon layer of the positive electrode material with only flaky carbon coating is in the range of 100-290nm, and the gap distance between the flaky carbon layers is in the range of 1-92nm. In the positive electrode material with both flaky carbon coating and point-like carbon coating, the diameter of the point-like carbon coating is in the range of 1-62nm, the diameter of the flaky carbon coating is in the range of 100-290nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the total carbon content in the sodium positive electrode material is 1. The amount is 100wt%, the carbon content of the sodium ferrous sulfate coating is 95.1wt%, and the free carbon content is 4.9wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-650nm, the average size is 379nm, the size range of the secondary particles is 0.01-55μm, the average size is 30μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 61wt%, and the content of the secondary particles is 39wt%.
[0199] Embodiment 22
[0200] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, the pressing process of step S4 is omitted, and the precursor material is directly placed at 350° C. for 20 hours. The other process parameters are the same as those in embodiment 1.
[0201] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 5-50nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-30nm; in the sodium positive electrode material, the carbon layer coated on The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 30:70; the positive electrode material partially coated with the carbon layer includes positive electrode materials that are all carbon-coated in dots, sodium-based positive electrode materials that are all carbon-coated in flakes, and positive electrode materials with both carbon-coated dots and carbon-coated flakes in any proportion, wherein the diameter of the carbon layer in the positive electrode material coated with only carbon-coated dots is in the range of 1-65 nm, and the gap distance between the carbon-coated dots is in the range of 1-70 nm, the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-300nm, and the gap distance between the flake carbon layers is in the range of 1-90nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 1-65nm, the diameter of the flake carbon coating is in the range of 100-300nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-75nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 92wt%, and the content of free carbon is 8wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-300nm, the average size is 95nm, the size range of the secondary particles is 0.01-35μm, the average size is 15μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 90wt%, and the content of the secondary particles is 10wt%.
[0202] Embodiment 23
[0203] The difference between this embodiment and embodiment 1 is that in the preparation method provided in this embodiment, step S2 adopts wet mixing and dissolving 4000g of the pretreated sodium sulfate obtained in step S1 with 1000g of glucose and 10kg of water, and then spray drying the wet mixed material, and then sintering the spray dried product at 600°C for 8h, and the sintering is carried out under a nitrogen atmosphere to obtain in-situ carbon-coated sodium sulfate. The remaining process parameters are the same as those in embodiment 1.
[0204] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 5wt%, the sodium positive electrode material comprising a positive electrode material with a carbon layer coated on the entire surface of sodium ferrous sulfate and a positive electrode material with a carbon layer coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 2-45nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 1-25nm; in the sodium positive electrode material, the carbon layer coated on the sodium ferrous sulfate The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with a carbon layer on a partial surface of sodium ferrous sulfate is 40:60; the positive electrode material partially coated with a carbon layer includes positive electrode materials that are all carbon-coated in a point-like manner, sodium-based positive electrode materials that are all carbon-coated in a sheet-like manner, and positive electrode materials that are both carbon-coated in a point-like manner and carbon-coated in a sheet-like manner, wherein the diameter of the carbon layer in the positive electrode material that is only carbon-coated in a point-like manner ranges from 40 to 95 nm, and the gap distance between the carbon layers in a point-like manner ranges from 1 to 35 nm , the diameter of the carbon layer of the positive electrode material with only flake carbon coating is in the range of 100-486nm, and the gap distance between the flake carbon layers is in the range of 1-46nm. In the positive electrode material with both flake carbon coating and point carbon coating, the diameter of the point carbon coating is in the range of 40-95nm, the diameter of the flake carbon coating is in the range of 100-486nm, and the gap distance between the point carbon layer and the flake carbon layer is in the range of 1-35nm; free carbon is also included in the sodium positive electrode material, and the total carbon content in the sodium positive electrode material is 1. The content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 95wt%, and the free carbon content is 3.5wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-450nm, the average size is 316nm, the size range of the secondary particles is 0.01-48μm, the average size is 24μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 68wt%, and the content of the secondary particles is 32wt%.
[0205] Embodiment 24
[0206] The preparation method of the sodium positive electrode material provided in this embodiment comprises the following steps:
[0207] (A) Anhydrous sodium sulfate is placed at 200° C. for a first drying for 10 hours, and then the anhydrous sodium sulfate after the first drying is crushed under nitrogen protection with a nitrogen gas flow with a gas flow pressure of 1.5 MPa for 10 minutes until the particle size D50 of the anhydrous sodium sulfate is 0.8 μm, thereby obtaining pretreated sodium sulfate for standby use.
[0208] The ferrous sulfate heptahydrate was placed at 350° C. for a second drying for 10 hours to obtain anhydrous ferrous sulfate, and then the obtained anhydrous ferrous sulfate was crushed under nitrogen protection with a nitrogen gas flow with a gas flow pressure of 1.5 MPa for 10 minutes until the particle size D50 of the anhydrous ferrous sulfate was 0.8 μm, thereby obtaining pretreated ferrous sulfate for use;
[0209] (B) 4000 g of the pretreated sodium sulfate obtained in step (A), 1000 g of glucose, 3028 g of the pretreated ferrous sulfate obtained in step (A), and 152 g of ascorbic acid were premixed in a high-speed mixer, and then ball-milled at a rotation speed of 400 rpm for 6 hours to obtain a precursor material.
[0210] (C) The precursor material obtained in step (B) is loaded into a hot pressing mold, and the material and the mold are placed in a hot pressing furnace, pressurized to 100 MPa, and heated to 350° C. to perform hot pressing sintering on the precursor material for 12 hours, and then cooled to 150° C. to take out the material, and then, the taken out material is crushed, and then sieved with a sieve with a mesh size of 325 to obtain a carbon-coated sodium ferrous sulfate sodium positive electrode material.
[0211] The sodium positive electrode material obtained by the above preparation method in this embodiment includes carbon-coated sodium ferrous sulfate, whose chemical formula is Na 2.56 Fe 1.72(SO4)3@C, with the total mass of the sodium positive electrode material being 100wt%, the mass of the carbon layer coated on the surface of the base material being 8wt%, the sodium positive electrode material comprising a positive electrode material in which the carbon layer is coated on the entire surface of sodium ferrous sulfate and a positive electrode material in which the carbon layer is coated on a portion of the surface of sodium ferrous sulfate, the thickness of the carbon layer coated on the entire surface of sodium ferrous sulfate being in the range of 10-75nm, and the thickness of the carbon layer coated on a portion of the surface of sodium ferrous sulfate being in the range of 10-65nm; in the sodium positive electrode material, the carbon layer coating The mass ratio of the positive electrode material on the entire surface of sodium ferrous sulfate to the positive electrode material coated with the carbon layer on a part of the surface of sodium ferrous sulfate is 60:40; the positive electrode material partially coated with the carbon layer includes positive electrode materials with all point-like carbon coatings in any proportion, sodium positive electrode materials with all sheet-like carbon coatings, and positive electrode materials with both point-like carbon coatings and sheet-like carbon coatings, wherein the diameter of the carbon layer in the positive electrode material coated with only point-like carbon is in the range of 30-99nm, and the gap distance between the point-like carbon layers is in the range of 1-25 nm, the diameter of the carbon layer of the positive electrode material with only flaky carbon coating is in the range of 100-650nm, and the gap distance between the flaky carbon layers is in the range of 1-35nm. In the positive electrode material with both flaky carbon coating and point-like carbon coating, the diameter of the point-like carbon coating is in the range of 30-99nm, the diameter of the flaky carbon coating is in the range of 100-650nm, and the gap distance between the point-like carbon layer and the flaky carbon layer is in the range of 1-30nm; free carbon is also included in the sodium positive electrode material, and the carbon in the sodium positive electrode material is The total content is 100wt%, the carbon content used for coating sodium ferrous sulfate is 80wt%, and the content of free carbon is 20wt%; the sodium positive electrode material includes primary particles and secondary particles, the size range of the primary particles is 1-700nm, the average size is 463nm, the size range of the secondary particles is 0.01-78μm, the average size is 61μm, and the total content of the total particles of the sodium positive electrode material is 100%, the content of the primary particles is 45wt%, and the content of the secondary particles is 55wt%.
[0212] Comparative Example 1
[0213] The sodium positive electrode material provided in this comparative example is different from that in Example 1 only in that the sodium positive electrode material provided in this comparative example omits the carbon layer coating and is only a sodium ferrous sulfate positive electrode material, with a chemical formula of Na 2.56 Fe 1.72 (SO4)3.
[0214] This comparative example provides a method for preparing the above-mentioned sodium positive electrode material, comprising the following steps:
[0215] Step 1: S1. Place anhydrous sodium sulfate at 200° C. for a first drying for 10 hours, then crush the anhydrous sodium sulfate after the first drying under nitrogen protection with a nitrogen gas flow at a gas flow pressure of 1.5 MPa for 10 minutes until the particle size D50 of the anhydrous sodium sulfate is 0.8 μm, and the pretreated sodium sulfate is obtained for standby use.
[0216] The ferrous sulfate heptahydrate was placed at 350° C. for a second drying for 10 hours to obtain anhydrous ferrous sulfate, and then the obtained anhydrous ferrous sulfate was crushed under nitrogen protection with a nitrogen gas flow with a gas flow pressure of 1.5 MPa for 10 minutes until the particle size D50 of the anhydrous ferrous sulfate was 0.8 μm, thereby obtaining pretreated ferrous sulfate for use;
[0217] Step 2: Weigh 2022 g of pretreated sodium sulfate, 3028 g of pretreated ferrous sulfate, and 152 g of ascorbic acid, premix them in a high-speed mixer, and then grind them in a planetary ball mill for 6 hours to obtain a precursor material;
[0218] The third step: compact the obtained precursor material and load it into a hot pressing mold, place the material together with the mold in a hot pressing furnace, pressurize it to 100 MPa, and heat it to 350°C to perform hot pressing sintering on the precursor material for 12 hours, then cool it to 150°C to take out the material, then crush the taken out material, and then sieve it with a sieve with a mesh size of 325 to obtain the sodium iron sulfate positive electrode material.
[0219] The sodium positive electrode materials obtained in Examples 1-24 and Comparative Example 1 were tested for compaction density, water content and specific surface area. The specific testing process was as follows:
[0220] (1) Testing process of compaction density: The compaction density of the sodium positive electrode material is tested using automatic compaction density testing equipment;
[0221] (2) Testing process of H2O water content: The water content in the sodium battery positive electrode material is tested using the Karl Fischer water content test method;
[0222] (3) Specific surface area (BET) testing process: The specific surface area of the sodium cathode material is tested using the BET method;
[0223] (4) Purity testing process: The content of unreacted material and the content of sodium-rich impurities are calculated by XRD, and the total element content and other impurity element content are calculated by inductively coupled plasma emission spectroscopy (ICP analysis). The purity of the obtained sodium positive electrode material can be calculated by the calculation formula: purity of sodium positive electrode material = (total product mass - impurity element content - unreacted material content - sodium-rich impurity phase content) / total product mass × 100%.
[0224] The test results are shown in Table 1.
[0225] Table 1
[0226]
[0227]
[0228] Application Examples 1-24 and Comparative Application Example 1
[0229] The sodium positive electrode materials obtained in Examples 1-24 and Comparative Example 1 are assembled into sodium ion positive electrode materials, wherein the preparation process of the positive electrode is as follows: the sodium positive electrode materials obtained in Examples 1-24 and Comparative Example 1 are mixed with conductive carbon black (SP) and PVDF in a weight ratio of 80wt%:10wt%:10wt%, and N-methylpyrrolidone NMP is used as a solvent to obtain a positive electrode slurry by dispersion, and the obtained positive electrode slurry is coated on an aluminum foil current collector, and a surface density of 7.8g / cm is prepared by rolling. 3 The positive electrode sheet is then punched into a small disc with a diameter of 12 mm using a film mold, and after drying and weighing, the positive electrode is obtained; the negative electrode is metallic sodium; the electrolyte is a solvent of ethylene carbonate and propylene carbonate with a volume ratio of 1:1, and the electrolyte mass salt is 1 mol / L sodium hexafluorophosphate. The above positive electrode, negative electrode and electrolyte are assembled into a 2025 button battery shell to form a sodium ion battery.
[0230] The sodium ion battery assembled in the corresponding use case 1-24 and comparative application example 1 was left standing for 4 hours at 25°C, and then the first charge and discharge capacity test was carried out. The test conditions were: 0.1C charging to 4.5V, constant voltage charging to 0.025C cut-off, standing for 3 minutes, 0.1C discharge to 2.0V, and the charge and discharge specific capacity was obtained. The first charge gram capacity C0 and the first discharge gram capacity D0 of 2-4.5V were recorded respectively, and the first coulomb efficiency was calculated according to D0 / C0, and the capacity retention rate was recorded at a voltage of 2-4.5V and a 5C rate for 500 cycles. The test results are shown in Table 2.
[0231] Table 2
[0232]
[0233]
[0234] From the test results in Table 1 and Table 2, we can see that:
[0235] (1) It can be seen from Examples 1 to 9 and Application Examples 1 to 9 that the sodium cathode material provided by the present invention is coated with a carbon layer on the surface of the base material, which improves the stability and conductivity of the material. Furthermore, by adjusting the form of carbon coating, the partial coating and full coating of the carbon layer on the surface of the base material are coordinated with each other, combined with the specific form of partial carbon coating, the conductivity of the sodium cathode material is improved while improving the transmission of sodium ions inside the material, so that the sodium cathode material can have the advantages of both excellent capacity performance and stable cycle performance.
[0236] Figure 2 The following is a scanning electron microscope image of the in-situ carbon-coated sodium sulfate obtained in Example 1. Figure 3 for Figure 2 The corresponding energy dispersive X-ray spectrum of carbon is given by Figure 2 Combination Figure 3 It can be seen that a large amount of carbon layer is in situ coated on the surface of sodium sulfate particles.
[0237] Figure 4 It is the X-ray diffraction spectrum of the sodium positive electrode material prepared in Example 1. As can be seen from the figure, the peak in the X-ray diffraction spectrum of the sodium positive electrode material prepared in Example 1 corresponds to the standard card PDF#-01-085-6588, confirming that the carbon-coated sodium positive electrode material obtained is sodium ferrous sulfate.
[0238] Figure 5 and Figure 7 The following are scanning electron microscope images of the sodium positive electrode material prepared in Example 1 at different magnifications. Figure 6 for Figure 5 The corresponding energy dispersive X-ray spectrum of carbon is given by Figure 5 , Figure 6 and Figure 7 It can be seen that the surface of the particles of the obtained sodium positive electrode material is in situ coated with a large number of carbon layers, a part of the surface of the sodium ferrous sulfate is partially coated with a carbon layer, and a part of the surface of the sodium ferrous sulfate is fully coated with a carbon layer, and through Figure 5 and Figure 7 It can be seen from the scanning electron microscope image that the carbon layer coated on the surface of sodium ferrous sulfate exists in two forms: point-shaped and flake-shaped.
[0239] Figure 8The charge and discharge curves of the sodium ion batteries provided in Application Examples 1 and 4-7 at 0.1C are given. It can be seen from the figure that the positive electrode material used in the sodium ion battery provided in Application Examples 4-7 controls the quality of the first raw material sodium sulfate and the organic carbon source glucose during the preparation process. It can be seen from the charge and discharge curves of Application Examples 1 and 4-7 that controlling the amount of organic carbon source added relative to the first raw material and controlling the carbon coating amount within a reasonable range will affect the charge and discharge performance of the resulting sodium ion battery, but still maintain relatively excellent electrochemical properties.
[0240] Fig. 9 It is a charge and discharge curve diagram of the sodium ion battery provided in Application Example 1 and Application Examples 8-9 at 0.1C. It can be seen from the figure that the positive electrode material used in the sodium ion battery provided in Application Example 8 appropriately reduces the hot pressing sintering temperature and extends the insulation time during the preparation process, and its charge and discharge curve is close to the charge and discharge curve of Application Example 1, indicating that Application Example 8 still has relatively excellent electrochemical performance; the positive electrode material used in the sodium ion battery provided in Application Example 9 adopts a hot pressing sintering process of first pressing and then sintering during the preparation process. Although the charge and discharge performance is lower than that of Application Example 1, it still has relatively excellent performance effects.
[0241] (2) By comparing Example 1 with Example 10-11, and Application Example 1 with Application Example 10-11, it can be seen that if the pretreatment process of drying and crushing sodium sulfate is omitted in the present invention, the material reaction will be insufficient, and the water content of the obtained sodium positive electrode material will increase, thereby reducing the electrochemical performance of the positive electrode material; if the pretreatment process of drying and crushing ferrous sulfate is omitted, the material reaction will be insufficient, and the water content of the obtained sodium positive electrode material will also increase, thereby reducing the electrochemical performance of the material.
[0242] (3) By comparing Example 1 with Example 12-13 and Application Example 1 with Application Example 12-13, it can be seen that the present invention controls the coating amount of the carbon material by controlling the mass ratio of the first raw material and the organic carbon source. If the mass ratio of the two is too large and the amount of carbon added is too small, the proportion of the positive electrode material of the entire carbon layer coated on the surface of the sodium ferrous sulfate is low, the specific surface area of the sodium positive electrode material is reduced, and the compaction density is increased, but the water content of the sample is increased, and the conductivity of the material is reduced, thereby reducing the capacity rate performance and cycle stability of the sodium ion battery; if the mass ratio of the two is too low, the carbon coating amount is increased, and the proportion of the positive electrode material in which the carbon layer in the sodium positive electrode material is completely coated on the surface of the ferrous sulfate increases, the specific surface area of the sodium positive electrode material is increased, the compaction density is reduced, the water content is reduced, and the conductivity of the material is enhanced, but the coating of too many carbon layers will hinder the diffusion and transmission of sodium ions in the material, thereby reducing the capacity rate performance and cycle stability of the sodium ion battery.
[0243] (4) By comparing Example 1 with Examples 14-15, and Application Example 1 with Application Examples 14-15, it can be seen that in the present invention, if the sintering temperature after the solid-phase mixing of the first raw material and the organic carbon source is too low, the degree of graphitization of the organic carbon source will be low, thereby making the conductivity of the obtained sodium positive electrode material poor, and further resulting in poor electrochemical performance of the constructed sodium ion battery; if the sintering temperature is too high, sodium sulfate will decompose, making it difficult to subsequently synthesize high-purity carbon-coated sodium ferrous sulfate.
[0244] Fig.10 The charge and discharge curves of the sodium ion batteries provided in Application Examples 1 and 14 at 0.1C are given. It can be seen from the figure that, compared with Application Example 1, the positive electrode material used in the sodium ion battery provided in Application Example 14 reduces the sintering temperature after the solid phase mixing of the first raw material and the organic carbon source during the preparation process, which will cause the charge and discharge performance of the sodium ion battery to deteriorate.
[0245] (5) By comparing Example 1 and Examples 16-17, and Application Example 1 and Application Examples 16-17, it can be seen that the present invention regulates the amount of antioxidant added. If the amount of antioxidant added is too low, the raw materials will be oxidized during the preparation process, affecting the material's own performance and electrochemical properties; if the amount of antioxidant added is too high, the content of amorphous carbon with poor conductivity will be too high, which will reduce the compaction of the material, increase the specific surface area, and be unfavorable for electron transport, resulting in a decrease in the electrochemical performance of the sodium cathode material.
[0246] (6) By comparing Example 1 and Examples 18-19, and Application Example 1 and Application Examples 18-19, it can be seen that if the pressure of pressing the precursor material of the present invention is too low, it will lead to insufficient reaction of the raw materials, poor consistency of the product, and reduced purity; if the pressure of pressing the precursor material is too high, the hardness of the sample will be too high, which will make it difficult to crush it later, resulting in excessively large particles, and the sample will be unable to exert its performance.
[0247] (7) By comparing Example 1 with Examples 20-21, and Application Example 1 with Application Examples 20-21, it can be seen that if the sintering temperature of the precursor material is too low, sodium ferrous sulfate cannot be synthesized and the performance of the finished product is extremely poor; if the sintering temperature of the precursor material is too high, sodium ferrous sulfate will decompose, the purity of the sodium positive electrode material will be significantly reduced, and the electrochemical performance will deteriorate.
[0248] (8) By comparing Example 1 and Example 22, and Application Example 1 and Application Example 22, it can be seen that if the pressing and sintering process of the precursor material of the sodium cathode material provided by the present invention is replaced by a sintering process, and the pressing process is omitted, due to the obstruction of the in-situ carbon coating layer of the first raw material, atomic diffusion is difficult, and the first raw material and the second raw material cannot fully react, resulting in a decrease in the purity of the sodium cathode material in the obtained product, thereby causing the electrochemical performance of the sodium ion battery to deteriorate.
[0249] Fig.11 The charge and discharge curves of the sodium ion batteries provided in Application Example 1 and Application Example 22 at 0.1C are given in the figure. It can be seen that compared with Application Example 1, the positive electrode material used in the sodium ion battery provided in Application Example 22 replaces the pressing and sintering process of the precursor material with a sintering process during the preparation process, and omits the pressing process, which will cause the electrochemical performance of the sodium ion battery to deteriorate and the cycle capacity to decrease.
[0250] (9) By comparing Example 1 and Example 23, and Application Example 1 and Application Example 23, it can be seen that if the solid-phase mixing of the first raw material and the organic carbon source in the present invention is replaced by a wet mixing process combined with a spray drying process, the specific surface area of the sodium-based positive electrode material will be too large and the compaction density will be too low, thereby deteriorating the electrochemical performance of the sodium-ion battery.
[0251] (10) By comparing Example 11 and Example 24, and Application Example 1 and Application Example 24, it can be seen that if the first raw material, the second raw material, the organic carbon source and the antioxidant are directly mixed to prepare the carbon-coated sodium ferrous sulfate positive electrode material and combined with a 350°C hot pressing sintering process, the degree of graphitization of the organic carbon source will be reduced, and the form and morphology of the carbon layer coating in the sodium positive electrode material will be affected, thereby affecting the performance of the obtained positive electrode material itself and the performance of the constructed sodium ion battery.
[0252] (11) By comparing Example 1 with Comparative Example 1, and Application Example 1 with Comparative Application Example 1, it can be seen that if the present invention directly mixes the first raw material and the second raw material to form a pure sodium iron sulfate positive electrode material, but lacks in-situ carbon coating, the water content of the obtained sodium positive electrode material will be greatly increased, and the conductivity of the material will be deteriorated, thereby causing its capacity in sodium ion batteries to be low.
[0253] Fig.11 The charge and discharge curves of the sodium ion batteries provided in Application Example 1 and Comparative Application Example 1 at 0.1C are given. It can be seen from the figure that, compared with Application Example 1, the positive electrode material used in the sodium ion battery provided in Comparative Application Example 1 directly mixes the first raw material and the second raw material during the preparation process, and omits the in-situ carbon coating, which will cause the charge and discharge performance of the sodium ion battery to deteriorate and the capacity to be lower.
[0254] In summary, the sodium-based positive electrode material provided by the present invention is coated with a carbon layer on the surface of the base material, which can improve the stability of the sodium-based positive electrode material and improve the conductivity of the material itself, and further control the form of carbon coating. Through the mutual coordination of partial carbon coating and full carbon coating on the base material, the partial coating is further regulated to adopt a specific form of sheet and / or point, which can ensure that the sodium-based positive electrode material has excellent conductivity and stability, and can also promote the effective transmission of sodium ions in the material, and improve the deintercalation of sodium ions inside the material, so that the sodium-based positive electrode material can have multiple advantages of excellent capacity performance and stable cycle performance.
[0255] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A sodium positive electrode material, characterized in that: The sodium positive electrode material comprises a base material and a carbon layer coated on the surface of the base material; The chemical formula of the matrix material is Na 2+2x Fe 2-x M3, where M is a polyanion, 0≤x<2; The sodium-based positive electrode material includes a first sodium-based positive electrode material and a second sodium-based positive electrode material. The carbon layer on the surface of the base material in the first sodium-based positive electrode material is fully coated, and the carbon layer on the surface of the base material in the second sodium-based positive electrode material is partially coated. The coating morphology of the partially coated carbon layer includes dots and / or flakes.
2. The sodium positive electrode material according to claim 1, characterized in that The M comprises a sulfate anion; Preferably, the total mass of the sodium positive electrode material is 100wt%, and the mass percentage of the carbon layer coated on the surface of the base material is 0.1-20wt%; Preferably, in the sodium positive electrode material, the mass ratio of the first sodium positive electrode material to the second sodium positive electrode material is (5-50):(50-95); Preferably, the thickness of the carbon layer in the first sodium-based cathode material and the carbon layer in the second sodium-based cathode material are independently selected from 1-50 nm; Preferably, when the partially coated morphology of the carbon layer is dot-shaped, the diameter of the carbon layer is 1-100 nm, excluding 100 nm, and the gap distance between the carbon layers is 1-200 nm; Preferably, when the partially coated morphology of the carbon layer is in the form of a sheet, the diameter of the carbon layer is 100-500 nm, and the gap distance between the carbon layers is 1-200 nm; Preferably, when the partial coating of the carbon layer is in the form of dots and flakes, the diameter of the dot-shaped carbon layer is 1-100 nm, excluding 100 nm, and the diameter of the flake-shaped carbon layer is 100-500 nm; Preferably, when the partial coating morphology of the carbon layer is dot-shaped and flake-shaped, the gap distance between the dot-shaped carbon layer and the flake-shaped carbon layer is 1-200 nm.
3. The sodium positive electrode material according to claim 1 or 2, characterized in that: The compaction density of the sodium positive electrode material at 3T pressure is 1.8-2.36 g / cm 3 ; Preferably, the specific surface area of the sodium positive electrode material is 5-30m 2 / g; Preferably, the sodium cathode material also includes free carbon; Preferably, the total carbon content in the sodium positive electrode material is 100wt%, and the carbon content coated on the surface of the base material is 10-99wt%; Preferably, the total carbon content in the sodium positive electrode material is 100wt%, and the carbon content of the free carbon is 1-50wt%.
4. The sodium positive electrode material according to any one of claims 1 to 3, characterized in that: The sodium positive electrode material comprises primary particles and secondary particles; Preferably, the size of the primary particles is 0.001-1 μm; Preferably, the size of the secondary particles is 0.01-100 μm; Preferably, based on the total content of the total particles of the sodium positive electrode material being 100%, the content of the primary particles is 5-90wt%; Preferably, the total content of the total particles of the sodium positive electrode material is 100wt%, and the content of the secondary particles is 1-80wt%.
5. A method for preparing a sodium positive electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) solid-phase mixing a first raw material with an organic carbon source, and sintering the mixture to obtain an intermediate having in-situ carbon coating; the first raw material provides sodium ions and polyanions; (2) performing a secondary solid phase mixing of the intermediate having in-situ carbon coating with a second raw material and an antioxidant to obtain a precursor material; the second raw material provides ferrous ions and polyanions; (3) Pressing and sintering the precursor material to obtain the sodium positive electrode material.
6. The preparation method according to claim 5, characterized in that: Step (1) The first raw material includes sodium sulfate; Preferably, in step (1), the first raw material is also pretreated before the first solid-phase mixing; Preferably, the specific process of pre-treating the first raw material includes: performing a first drying on the first raw material, and then performing a first crushing to obtain the pre-treated first raw material; Preferably, the temperature of the first drying is 200-350°C; Preferably, the first drying time is 1-15h; Preferably, the particle size D50 of the first raw material after the first crushing is less than 1 μm; Preferably, the first crushing is performed in nitrogen and / or inert gas; Preferably, the organic carbon source in step (1) comprises any one of glucose, ascorbic acid, citric acid, tea polyphenols or starch, or a combination of at least two thereof; Preferably, in step (1), the mass ratio of the first raw material to the organic carbon source is (50-95):(5-50); Preferably, before the first solid phase mixing in step (1), the first raw material and the organic carbon source are first premixed; Preferably, the sintering temperature in step (1) is 500-800°C; Preferably, the sintering time in step (1) is 4-10 hours; Preferably, the sintering atmosphere in step (1) is a nitrogen atmosphere and / or an inert atmosphere.
7. The preparation method according to claim 5 or 6, characterized in that: Step (2) the second raw material comprises ferrous sulfate; Preferably, in step (2), the second raw material is also pretreated before the secondary solid phase mixing; Preferably, the specific process of pre-treating the second raw material includes: performing a second drying on the second raw material, and then performing a second crushing to obtain the pre-treated second raw material; Preferably, the second drying temperature is 200-350°C; Preferably, the second drying time is 1-15h; Preferably, the particle size D50 of the second raw material after the second crushing is less than 1 μm; Preferably, the second crushing is performed in nitrogen and / or inert gas.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The molar ratio of the intermediate with in-situ carbon coating in step (2) to the second raw material is 1:(1-2); Preferably, the antioxidant is added in an amount of 0.01-10wt% of the mass of the second raw material; Preferably, the antioxidant comprises any one of ascorbic acid, citric acid or tea polyphenols or a combination of at least two thereof; Preferably, before the second solid phase mixing in step (2), the intermediate with in-situ carbon coating, the second raw material and the antioxidant are also subjected to a second premixing; Preferably, the specific process of pressing and sintering in step (3) includes: pressing the precursor material first and then sintering it, or pressing and sintering the precursor material at the same time; Preferably, the pressing pressure is 50-500MPa; Preferably, the sintering temperature is 280-380°C; Preferably, the product obtained after pressing and sintering in step (3) is also crushed and sieved.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the sodium positive electrode material according to any one of claims 1 to 4, or the sodium positive electrode material prepared by the preparation method according to any one of claims 5 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Carbon nanosheet material and preparation thereof, and application of carbon nanosheet material in sodium-ion battery
CN108011105A
Solid-state sodium ion battery
CN116779841A
Sodium-rich carbon-coated sodium ferrous sulfate positive electrode material as well as preparation method and application thereof
CN117855415A
Positive electrode material, preparation method, pole piece and battery
CN117936740A
Carbon-coated sodium vanadium fluorophosphate positive electrode material and preparation method thereof, positive electrode plate and secondary battery
CN119008903A